Dampak Politik Uang Terhadap Mahalnya Biaya Pemenangan Pemilu dan Korupsi Politik - Putri Sjafrina, Almas Ghaliya (Integritas : Jurnal Antikorupsi, 2019)
Money politics has posed a major challenge in Indonesian general election, which has not only dangerously polluted the election’s integrity but also triggered the emergence of political corruption. There have been at least 13 corruption cases handled by KPK with correlation with the costs to win the election, including the practice of nomination buying and vote buying. This article examines the correlation between money politics and political corruption, and suggests the importance of political parties’ reform as a necessary solution, particularly regarding the recruitment of election candidates, political party financing, and voter education. This agenda is important because the roots of nomination and vote buying mainly come from political parties’ problems. Keywords: Money Politics, Nomination Buying, Vote Buying, Political Corruption, Political Party, Voter Education